2005
DOI: 10.1227/01.neu.0000186950.54075.3b
|View full text |Cite
|
Sign up to set email alerts
|

Concussion in Professional Football: Brain Responses by Finite Element Analysis: Part 9

Abstract: Finite element modeling showed the largest brain deformations occurred after the primary head acceleration. Midbrain strain correlated with memory and cognitive problems and removal from play after concussion. Concussion injuries happen during the rapid displacement and rotation of the cranium, after peak head acceleration and momentum transfer in helmet impacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
189
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 261 publications
(203 citation statements)
references
References 101 publications
11
189
3
Order By: Relevance
“…This was from a player concussed on a kick return who had brief LOC, and PCS symptoms of headache, fatigue, dizziness, and photophobia and sleep disorder as physical symptoms. Note that the modeling of this subjects brain would involve all of the structures identified in Figure 1, and indeed, the high strain findings modeled in this subject supported such a locus of injury (see Appendix 1B of the Viano et al, 2005b paper that detail individual characteristics of the subjects).…”
Section: Pathophysiology Of Concussionmentioning
confidence: 64%
See 4 more Smart Citations
“…This was from a player concussed on a kick return who had brief LOC, and PCS symptoms of headache, fatigue, dizziness, and photophobia and sleep disorder as physical symptoms. Note that the modeling of this subjects brain would involve all of the structures identified in Figure 1, and indeed, the high strain findings modeled in this subject supported such a locus of injury (see Appendix 1B of the Viano et al, 2005b paper that detail individual characteristics of the subjects).…”
Section: Pathophysiology Of Concussionmentioning
confidence: 64%
“…The Viano et al (2005b) modeling study found, in general, excursions of the concussed brain to be between 3-6 mm at 24-26 ms post-impact. Of particular importance to neuropsychology is that this modeling shows 4-5 mm displacements of the hippocampus, caudate, amygdala, anterior commissure, and midbrain (again refer to Fig.…”
Section: Physics Of Tbimentioning
confidence: 91%
See 3 more Smart Citations